Epidemiological analysis of Lambert-Eaton myasthenic syndrome in Türkiye: insights from a nationwide electronic health database - Berin Inan; Bilgin Ozturk; Naim Ata; Suayip Birinci; Erdal Eroglu; Omer Karadas; Ersin Tan; Zeki Odabasi (Frontiers in Neurology)
IntroductionLambert-Eaton myasthenic syndrome (LEMS) is a rare autoimmune disorder of the neuromuscular junction, with limited large-scale epidemiological data. In this study, we aimed to determine the epidemiological profile of LEMS in Türkiye, and to assess associated malignancies, mortality, and prescription rates of pyridostigmine and amifampridine.MethodsWe identified LEMS cases through a retrospective review of clinical records for individuals with a G73.1 code entry in the national healthcare database between 2015 and 2024. Confirmed cases were classified as autoimmune (A-LEMS) or paraneoplastic (P-LEMS). Demographic, clinical, and prescription data were analyzed, and incidence and prevalence rates were calculated using official census data.ResultsA total of 159 LEMS cases were confirmed. The median age at diagnosis was 60 years, and 55.3% of the patients were female. P-LEMS accounted for 59.7% of cases, with small cell lung cancer (SCLC) present in 55.8% of these. Annual incidence of LEMS ranged from 0.09 to 0.30 per million, and the overall 2024 prevalence was 1.11 per million. A-LEMS had a higher prevalence than P-LEMS in 2024, likely due to its lower mortality (23.4% vs. 58.9%). P-LEMS was more common in older males and predominantly associated with SCLC. Pyridostigmine was prescribed to 65.4% of patients, and amifampridine to 24.5%, with both treatments more frequently used in A-LEMS.DiscussionThis is the first nationwide epidemiological study of LEMS in Türkiye, revealing lower incidence and prevalence rates than in other countries. This study provides valuable large-scale epidemiological data, enriching the global understanding of this rare disorder.